Pengaruh Pendekatan Pembelajaran Sosial Emosional terhadap Pengembangan Karakter Siswa di Era Digital - Katrimah Katrimah (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to systematically examine the impact of the Social Emotional Learning (SEL) approach on character development among students in the digital era. The method used is a Systematic Literature Review by analyzing 15 accredited scientific articles published between 2021 and 2025. The analysis results indicate that the implementation of SEL consistently has a positive impact on the development of character values, particularly empathy, responsibility, and adaptability. For example, several studies show that the integration of SEL in technology-based learning increases student empathy by 30%, enhances group collaboration skills by up to 45%, and reduces aggressive or uncooperative behavior by 25%. These character improvements tend to be more significant when SEL is implemented through interactive digital media that promotes active participation, self-reflection, and collaborative problem-solving. The novelty of this research lies in its focus on the integration of SEL within digital learning contexts, which is increasingly relevant amid the rapid advancement of educational technology. This study provides both theoretical and practical contributions for educators and policymakers in designing learning strategies that balance technological proficiency with the holistic strengthening of students’ character.